Studi Pengaruh Pemberian Bakteri Probiotik Komersial Terhadap Perubahan Kadar BOD dan COD Pada Air Limbah Tahu Dengan Perbedaan Interval Waktu Inkubasi 8 Jam - Harviel Adzan Megantyaka; Budi Utomo; Solichin Solichin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Environmental pollution has become a serious problem in the world, including in Indonesia. Tofu waste is waste from processing soybeans and consists of solid and liquid waste. Solid waste in the form of dirt left over from cleaning is usually called tofu dregs, while liquid waste is water resulting from washing tofu. Industry knows that disposing of waste directly into water bodies can pollute those waters, because it can lower the pH of the air and affect aquatic biota. Therefore, the industry knows that it must carry out processing first to prevent environmental problems. In this study, researchers used commercial probiotic bacteria to reduce BOD and COD levels in tofu wastewater. The research was carried out by testing in the laboratory and using statistical data with graphic methods which can provide a comparison of the water content of tofu waste before and after it was given. The action given in the research was a ratio of 1:1, 1:2 and 1:3 water to tofu waste with commercial probiotic bacteria. Apart from that, researchers also added incubation times within each 8 hour interval, namely at 0 hours, 8 hours, 16 hours, 24 hours and 32 hours. The results of the research show that administering commercial probiotics can reduce BOD and COD levels in tofu wastewater. The most significant reduction occurred in a ratio of 1:3 in COD and BOD to 242.69 mg/lt and 148.00 mg/lt with an incubation time of 32 hours. This proves the commercial effect of probiotic bacteria to reduce BOD and COD levels so that it can help reduce environmental pollution, especially in the air.